Does leader disability status influence the operational performance of teams with individuals with disabilities? An empirical study in the apparel industry - Cole, Dustin; Narayanan, Sriram; Vickery, Shawnee (Journal of Operations Management, 2024)
AbstractThis research examines the impact of leader disability status on the operational performance of teams that include individuals with disabilities (IWD) using longitudinal micro‐data from an apparel manufacturing company in a competitive integrative employment environment. To aid in developing the research hypotheses and in interpreting the empirical findings, the quantitative analysis is complemented with qualitative data collected through interviews involving managers and workers with and without disabilities at the focal firm and two other large companies that employ IWD. A beneficial moderating effect of leader‐worker disability status similarity on team performance is hypothesized and subsequently tested using Prais‐Winsten regression. The results show that a leader with a disability has a potentially beneficial impact on team performance as the number of workers with disabilities in the team increases, resulting in improved productivity (measured in labor hours per garment) and quality (measured in operator defects per garment). The theoretical, managerial, and policy implications of the study provide actionable insights for the creation of an inclusive labor force.